1994
DOI: 10.1002/dev.420270602
|View full text |Cite
|
Sign up to set email alerts
|

Tonic immobility and high‐intensity calls in a precocial chick as a function of age, diet, and time of day

Abstract: Tonic immobility (TI) and high-intensity vocalizations are two antipredator behaviors employed by domestic chicks (Gallus gallus) which vary in their function and the proximate mechanisms that govern them. In the present study, we sought to determine the influence of age (3 or 10 days old), diet (control or tryptophan-free), and time of testing (A.M. or P.M.) on the duration of TI and the number of calls produced in domestic chicks. Older chicks remained immobile significantly longer than younger chicks as did… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…1999). Interestingly, TI has been found to exhibit a circadian rhythm in a variety of species (Hennig and Dunlap 1977; Hill et al . 1994; Stahlbaum et al .…”
Section: Introductionmentioning
confidence: 99%
“…1999). Interestingly, TI has been found to exhibit a circadian rhythm in a variety of species (Hennig and Dunlap 1977; Hill et al . 1994; Stahlbaum et al .…”
Section: Introductionmentioning
confidence: 99%
“…Although this procedure has been employed in a number of studies (e.g., Hill et al, 1994;Rovee et al, 1977;Rovee et al, 1976;Rovee-Collier et al, 1983), the interruption of tonic immobility may have caused a ceiling effect. The difference in duration of tonic immobility between chicks tested in the a.m. and the p.m. for those given light cues late in incubation may have been more pronounced if there had been no experimenter-imposed upper limit to tonic-immobility duration and chicks were allowed to terminate the behavior on their own.…”
Section: Resultsmentioning
confidence: 97%
“…The difference in duration of tonic immobility between chicks tested in the a.m. and the p.m. for those given light cues late in incubation may have been more pronounced if there had been no experimenter-imposed upper limit to tonic-immobility duration and chicks were allowed to terminate the behavior on their own. Hill et al (1994) examined the rate of vocalization of chicks during tonic immobility as a function of clock hour and found that chicks called at a significantly faster rate when tested during the day than at night. In the present study, the fact that birds exposed to light cues during the late stage of incubation called at a somewhat faster rate when they were tested during the a.m. than when tested at p.m., and more so than the other prehatch groups, provides further support for the endogenous clock beginning to function sometime after Day 13 of incubation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other psychobiological studies have suggested that neurotransmitters and endogenous substances could be involved in animal screaming. For example, a reduction in vocalization was noted in rats with increased endogenous opiates (Goodwin & Barr, 1997) and in chickens with a tryptophan-enriched diet, which raised their serotonin level (Hill, Fleming, & Shrier, 1994). On the other hand, an increase in vocalization was observed in mice that were administered an anticholinergic drug (Branchi, Campolongo, & Alleva, 2004).…”
Section: Screaming In Animals and Human Beingsmentioning
confidence: 99%